The inheritance and innovation of horse-faced skirt culture in modern fashion style - Yanping, Gu (2025)
As one of the ancient traditional costumes of the Chinese nation, the horse-faced skirt has a lengthy history. From time immemorial to the present day, it has undergone an evolution from simplicity to complex decoration and gradually to splendour. However, with the development of modern civilization, the status of the horse-faced skirt has gradually declined, and it seems to be struggling in the process of constant confrontation with modern civilization. However, in today's world clothing arena, as internationally renowned designers such as Alexander Wang have begun to focus on the aesthetics of Eastern clothing, Chinese civilization is expected to take this opportunity to shine a fresh light on the international stage. It is worth noting that in 2022, a skirt released by Dior was suspected of plagiarizing a Chinese horse-faced skirt. The incident quickly caused an uproar on the Internet. "Dior plagiarism" became a hot topic and attracted widespread attention. This incident further highlights the special status and value of our horse-faced skirts. Instead of simply remaining in the past, it should move towards modernity and be accepted and used by more people as the times change and the needs change. In order to gain a deeper understanding of people's perceptions and attitudes towards horse-faced skirts, we conducted an offline survey and interviews with 250 women aged 18-50. According to the results, 67 percent of respondents were aware of the existence of the horse-face dress, but 85 percent had never worn it. Most do not yet have the awareness to make a purchase. This shows that although people have a certain understanding of horse-faced skirts, there are certain barriers to actual use and purchase. Therefore, this article aims to interpret the history of the horse skirt through additional analysis and explore its future innovative designs. We will focus on studying the style, craftsmanship, pattern and traditional color matching of the horse skirt, and pay attention to the innovation of every detail, striving to present a distinct design rather than a simple copy. We believe that a horse-face dress can also be filled with a youthful, stylish vibe and be in tune with the times. When people no longer reject it because of its tradition and heavyness, but genuinely love it for its cultural connotation, innovative design and practicality, the horse-faced skirt will usher in fresh life. Ultimately, we wanted to apply the techniques of dress mixing and matching, craftsmanship and colormatching to the innovative design of the horse-face dress to create a style that not only retained the traditional charm but also had a strong modern flavor. This will realize the traditional horse-faced skirt's use in the present and give it a modern meaning of the times.